Factors Relating to Compliance with Taking Drugs in Pulmonary TB Patients at Pauh Public Health Center - Alfita Dewi; Sri Handayani; Rima Julita; Chamy Rahmatiqa (Stikes Syedza Saintika Padang, 2022)
Complete treatment data for TB patients at the Pauh Health Center still has not reached the set target of 72%. This study aims to determine the factors related to medication adherence in pulmonary TB patients at the Pauh Health Center in 2022. This type of research was analytic with a cross sectional approach. The population in this study were all TB patients at the Pauh Health Center with a total of 40 people. The sampling technique used a total sampling technique. Data processing was carried out by computerization, data analysis was carried out univariate and bivariate using the Chi-Square test. The results of the study were almost half, namely 13 people (32.5%) of respondents who had a low level of adherence in taking TB drugs, 22 people (55.0%) of respondents who had a low level of knowledge, 26 people (65.0%) of respondents who do not work, 16 people (40.0%) respondents who get a bad role from health workers in taking TB drugs and 12 people (30.0%) respondents do not get family support in taking TB drugs. The conclusion of the study is that there is a relationship between knowledge (p 0.005), the role of health workers (p 0.023) and family support (p 0.003) and there is no relationship between work (p 0.778) with medication adherence in pulmonary TB patients. It is recommended for health workers to be more active in providing counseling about the importance of completing pulmonary TB treatment for 6 months.